The Students’ Anxiety Level in Speaking English in front of the class at Eleventh Grade of SMK Negeri 1 Meranti Kabupaten Asahan - Yuni Maslaila; Sipayung, Kammer; Tampubolon, Sahlan (The Explora, 2024)
This study aimed to investigate the levels of speaking anxiety among 11th-grade students at SMK Negeri 1 Meranti Kabupaten Asahan. Using a mixed-method approach, the study employs the modified Horwitz Foreign Language Classroom Anxiety Scale (FLCAS) to quantify anxiety levels and qualitative analysis to explore the specific types of anxiety and their triggers. This research used probability sampling to select 105 samples from a population of 142 students from 11th grade students of SMK Negeri 1 Meranti for the 2023 – 2024 academic year The findings revealed that (1)) the majority of students had very low anxiety levels (50.50%), moderately low anxiety (19.00%), moderate anxiety (17.10%), moderately high anxiety (9.50%), and high anxiety (3.90%) levels. The study concluded that speaking anxiety is a complex issue shaped by a combination of these internal and external variables.